Association of spiritual/religious coping with depressive symptoms in high‐ and low‐risk pregnant women. Issue 3 (7th December 2017) - Vitorino, Luciano M; Chiaradia, Raíssa; Low, Gail; Cruz, Jonas Preposi; Pargament, Kenneth I; Lucchetti, Alessandra L G; Lucchetti, Giancarlo
Abstract : Aims and objectives: To investigate the role of spiritual/religious coping (SRC) on depressive symptoms in high‐ and low‐risk pregnant women. Background: Spiritual/religious coping is associated with physical and mental health outcomes. However, only few studies investigated the role of these strategies during pregnancy and whether low‐ and high‐risk pregnant women have different coping mechanisms. Design: This study is a cross‐sectional comparative study. Methods: This study included a total of 160 pregnant women, 80 with low‐risk pregnancy and 80 with high‐risk pregnancy. The Beck Depression Inventory, the brief SRC scale and a structured questionnaire on sociodemographic and obstetric aspects were used. General linear model regression analysis was used to identify the factors associated with positive and negative SRC strategies in both groups of pregnant women. Results: Positive SRC use was high, whereas negative SRC use was low in both groups. Although we found no difference in SRC strategies between the two groups, negative SRC was associated with depression in women with high‐risk pregnancy, but not in those with low‐risk pregnancy. Furthermore, positive SRC was not associated with depressive symptoms in both groups. Conclusions: Results showed that only the negative SRC strategies of Brazilian women with high‐risk pregnancies were associated with worsened mental health outcomes. Relevance to clinical practice: Healthcare professionals, obstetricians and nurse midwives should focus on the use of negative SRC strategies in their pregnant patients.